The correlation between demographic factors and upper urinary tract stone composition in the Thai population - Noppon Arunkajohnsak (2020)
© 2020 Objective: To identify the correlation between demographic factors and upper urinary tract stone composition in the Thai population. Method: A retrospective observational study of first-time upper urinary tract stone former patients aged over 18 years who underwent stone surgery was performed in a tertiary referral university hospital from January 2013 to May 2018. Collected data included demographic information and stone composition information, which were analysed by the Fourier Transform-Infrared Spectroscopy (FTIR) method. The correlation between the demographic factors and major upper urinary tract stone composition was analysed using Fisher's exact test. Results: A total of 480 patients were included in this study. The stones were 319 (66.5%) renal calculi and 161 (33.5%) ureteric calculi. There were 248 (51.7%) single composition stones and 232 (48.3%) mixed composition stones. The major stone compositions were 288 (60.0%) calcium oxalate (CaOx), 125 (26.0%) calcium phosphate (CaP), 40 (8.3%) uric acid (UA), 19 (4.0%) magnesium ammonium phosphate (MAP), five (1.0%) cystine, and three (0.6%) ammonium hydrogen urate (AHU). Gender was correlated with the major stone composition. In females, a correlation was found between the major stone composition and age, diabetes mellitus (DM), and glomerular filtration rate (GFR). The study showed no significant correlation between the major stone composition and dyslipidemia (DLP), hypertension (HT), gout, and body mass index (BMI) in both genders. Conclusion: Gender, age, DM, and GFR were the factors affecting the stone composition.